Kontribusi Layanan Informasi dan Layanan Penempatan/Penyaluran terhadap Perencanaan Karier Siswa - Ayu Rahmaniah (Jurnal Konseling dan Pendidikan, 2013)
Planning a career in high school students can be developed with the implementation of services appropriate to their talents, interests and personal circumstances. This study aims to describe the contribution of information about career services and career placement services to the distribution of students' career planning is. This study includes a descriptive study, with a quantitative approach. Population were students of SMA Negeri 16 Padang class XI Academic Year 2012/2013 (243), with a total sample of 151 people, selected by simple random sampling technique. The instrument used was a questionnaire enclosed with the model using a Likert scale. The findings of the study is information about career services and placement services distribution contribute to the achievement levels of students are planning careers in the high category, it can be seen from the attitude toward career planning, career exploration attitudes, career decision making and understanding of information about the world of work.